An Advanced Medibox: Medicine Alert and Medicine Remainder Using Internet of Things - M. , Annamalai; B. , Sundaramurthy; S. , Sachin (International Journal of Psychosocial Rehabilitation, 2020)
The well-being and health segment is basic to human culture, and as such ought to be one of the first to get the advantages of up-and-coming advancements like IoT. A portion of the Internet of Medical Things (IoMT) is associated with IoT systems to screen the everyday exercises of the patients. As of late there has been an endeavor to structure new clinical gadgets that screen the drugs and assist mature people with superior healthy living. In this paper, one such endeavor is made to plan a multipurpose, canny gadget named MEDIBOX, which enables the patients to take their drugs at the correct time. This container is a capable framework that keeps up the parameters like temperature and stickiness in a controlled range suggested by the drug producer and accordingly keeps up the strength of the medicines. Identified with this, we have built up a Host Management System (HMS), which is fit for IoT observing that stores and controls the MEDIBOX’s usefulness for additional investigation and future change in plan perspectives. MEDIBOX takes control of alerting patients to take medicines by giving voice alerts and providing drive signs for the right medicines and maintains a strategic distance from the wrong meds at the wrong time. And furthermore affirms the medicine taken by the patient with timings. If the patient abstains from taking medicine at the right time, it sends an IoT alert to the guardian so as to assume responsibility for that circumstance and affirms the patient’s not skipping medicine.